The Influence Of Capital Structure And Profitability On Company Value At PT Astra Agro Lestari Tbk - Karolina Karolina; Arif Hidayat (Journal of International Multidisciplinary Research, 2024)
This study investigates how capital structure and profitability influence the value of PT Astra Agro Lestari Tbk. It employs a quantitative approach using numerical data, specifically analyzing the company's financial reports from 2012 to 2021. The findings indicate that capital structure significantly affects the company's value, with a T-test result showing a calculated value of 5.686, which exceeds the t-table value of 1.89458, and a significance level of 0.031 (less than 0.05). Profitability also has a significant impact, with a calculated value of 5.686 surpassing the t-table value of 1.89458 and a significance level of 0.001 (less than 0.05). This suggests that both capital structure and profitability individually affect the company's value. Additionally, when considered together, capital structure and profitability have a combined significant impact on firm value, with a significance level of 0.002 (less than 0.05) and a calculated F-value of 17.413, which is greater than the F-table value of 4.74. This confirms that both factors together significantly influence the company's value